2002
DOI: 10.1016/s0040816602000368
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the spermatozoa of Epipedobates flavopictus (Amphibia, Anura, Dendrobatidae), with comments on its evolutionary significance

Abstract: We describe, for the first time, the spermatozoon ultrastructure of a dendrobatid frog, Epipedobates flavopictus. Mature spermatozoa of E. flavopictus are filiform, with a moderately curved head and a proportionally short tail. The acrosomal vesicle is a conical structure that covers the nucleus for a considerable distance. A homogeneous subacrosomal cone lies between the acrosome vesicle and the nucleus. The nucleus contains a nuclear space at its anterior end, and electron-lucent spaces and inclusions. No pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 25 publications
5
30
1
2
Order By: Relevance
“…In the case of amphibians, frogs that fertilize in fresh water, such as Rana, tend to have simple sperm morphology [Poirier and Spink, 1971]. In contrast, urodeles [Picheral, 1979] and frogs with internal or terrestrial fertilization [Garda et al, 2002] tend to have more complicated sperm morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of amphibians, frogs that fertilize in fresh water, such as Rana, tend to have simple sperm morphology [Poirier and Spink, 1971]. In contrast, urodeles [Picheral, 1979] and frogs with internal or terrestrial fertilization [Garda et al, 2002] tend to have more complicated sperm morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on morphology, behaviour, sperm ultrastructure, cytogenetics and molecular analyses have been used to study dendrobatids in an attempt to elucidate their intra-family and inter-family relationships (Toft 1995;Zimmermann and Zimmermann 1988;Aguiar et al 2002Aguiar et al , 2003Aguiar et al , 2004aGarda et al 2002;Veiga-Menoncello et al 2003a,b, 2006a,b, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Several detailed studies on many taxa, including fishes (Jamieson 1991;Tanaka et al 1995), amphibians Lee and Jamieson 1993;Meyer et al 1997;Garda et al 2002), reptiles (Jamieson 1995;Teixeira et al 1999), annelids (Rouse and Jamieson 1987), and mollusks (Buckland-Nicks 1995), revealed that sperm ultrastructure provides an alternative source of useful characters for systematic purposes. According to Teixeira et al (1999), sperm ultrastructural characters contain significant phylogenetic information that can be profitably used in phylogenetic analyses for reptiles.…”
Section: Introductionmentioning
confidence: 99%